Synthetic strategies to achieve further-functionalised monoaryl phosphate primary building units: crystal structures and solid-state aggregation behavior. (2nd December 2014) - Dar, Aijaz A.; Mallick, Abhijit; Murugavel, Ramaswamy
Abstract : The synthesis of a new class of functionalized organophosphates, potential building units in materials and zeolite chemistry, has been reported. Abstract : New 4-halo functionalized 2, 6-diisopropyl phenyl phosphates, X-dippH2 [(RO)P(O)(OH)2 ] (R = 4-X-2, 6- i Pr2 C6 H3 ; X = Cl1, Br2, I3 ) have been synthesized in two steps starting from the corresponding 4-halophenols and characterized by analytical, spectroscopic, and single crystal X-ray diffraction studies. Isomorphous organophosphates1–3 form a tubular structure in the solid state through extensive hydrogen bonding interactions between adjacent –PO3 H2 groups, an aggregation previously unknown among organophosphates and phosphonic acids. The methyl ester of2, [(RO)P(O)(OMe)2 ] (R = 4-Br-2, 6- i Pr2 C6 H3 ) (4 ), was reacted with a series of boronic acids under Suzuki coupling conditions to yield the corresponding C–C bond coupled products, 3, 5-diisopropylbiphenyl-4-yl dimethyl phosphate (5 ), 4′-formyl-3, 5-diisopropyl-biphenyl-4-yl dimethyl phosphate (6 ) and 4′-(diphenylmethyleneamino)-3, 3′, 5, 5′-tetraisopropyl-biphenyl-4-yl dimethyl phosphate (7 ). The possible reaction conditions for the selective deprotection of phosphate triesters have been established, under which6 yields 4′-formyl-3, 5-diisopropyl-biphenyl-4-yl dihydrogenphosphate (8 ). Compound8 is a formyl group functionalized phosphate and shows hydrogen bonding similar to1–3 forming tubular channels surrounded by peripheral organic groups. The dangling formyl groups in phosphates6 and8 undergo intermolecular tail-to-tail hydrogen bonding forming 1-dimensional assemblies in the former and 3-dimensional supramolecules in the latter. Amino and formyl functionalized phosphates may serve as ideal primary building units for building suitably functionalized metal phosphate secondary building units.